A China como um duplo pólo na economia mundial e a recentralização da economia asiática - Carlos Aguiar de Medeiros (Brazilian Journal of Political Economy, 2006)
China as a double pole in the world economy and the recentralization of the Asian economy. The extraordinary growth of Chinese trade that occurred in the last years changed China’s role on world and regional economy. As a major producer of industrial consumer goods to OCDE countries, China has negatively affected many Asian competitors but as an expansive market China became the main source of growth to Asian countries. This new dimension was achieved after the Asian crisis of 1997 by an economic expansion led by public investment. After considering the Chinese balance of payment position and its industrial strategy this paper investigates this double dimension of China on trade and its influence on Asian countries.